An overview of primary registries of WHO's international clinical trial registry platform - Juneja, Atul (Ayu, 2019)
INTRODUCTION: WHO's International Clinical Trials Registry Platform (ICTRP) has 17 primary registries that collect the information on the minimum set of items of trial information that appear in the register and these registries are also endorsed by the International Committee of Medical Journal Editors. OBJECTIVE: The objective of this study is to describe the profile of all the primary registries including Clinical Trial Registry‑India (CTRI), through features such as magnitude, domain of registration, flagging, audit trail, language, mandatory requirements, and result disclosure. METHODOLOGY: The profiling of all registries was based on countries and zones, year of establishment, registrant, flagging, conflict of interest, language, documents, result disclosure, type of study, mode of registration, mandate of registration, quality check method, individual patient data statement and translation of content facility. The mode of search used was online which included advanced search, basic search and also from the audio/video manual on their website. RESULTS: There are 17 primary registries of ICTRP, the first one International Standard Randomised Controlled Trial Number (ISRCTN) of England being initiated in year 2000 and the most recent being Lebanese registry, in September 2019. The trials registered with these registries range from 301 in Cuba to 53972 in European union's EU Clinical Trials Register. The primary registries in WHO registry network are diverse in functionalities and practices. The characteristics of online registers vary in content and features and to achieve coordinated level of data quality, across all the different registries and to keep a balance in standards of the data collected and validation of that data, the registries are adhering to the minimum data set items laid down by ICTRP. CONCLUSION: The very process of registering the clinical studies helps in promoting the research methods and also raising the standards of research, especially among young researchers. It also helps in reducing the duplicity of research.